Improving Security in E-Transaction Blockchain Systems by Segmenting Processes into Separate Zones and Using Smart Contracts Arbitration - Jebbar, Wid Alaa; Al-Zubaidie, Mishall (Iraqi Journal of Science, 2025)
This study proposed an integrated security system for electronic transactions, first specifying the type of e-banking request using the two-phase commit procedure (2PC). The idea of micro-segmentation was then used to isolate individual e-transaction processes in different segments; after this, every segment was controlled by a smart contract. The Yellow Saddle Goatfish Algorithm (YSGA) was employed to detect whether the smart contract conditions were met optimally. Finally, if the customer receives approval, a distinct hash records the entire transaction procedure in the blockchain’s main ledger. In a simulation environment, the proposed system was tested, and the results were: 0.0031 ns as a time to detect the smart contract’s terms, an overall execution time between 0.001 ns and 0.005 ns, and a level of immutability equal to 5. The results of the analysis of the proposed system may inspire researchers/developers to apply it to e-banking institutions and benefit from the robust security features and high performance of the proposed methods.